Behavioral effects of transcranial pulsed current stimulation (tPCS): Speed-accuracy tradeoff in attention switching task. (August 2016) - Morales-Quezada, Leon; Leite, Jorge; Carvalho, Sandra; Castillo-Saavedra, Laura; Cosmo, Camila; Fregni, Felipe
Highlights: Active tPCS improved response time, but not accuracy on the attention switching task. This lack of effects on accuracy was also found on the paired associative learning. tPCS seems to increase efficiency but not efficacy on task performance. Abstract: Transcranial pulsed current stimulation (tPCS) has been shown to increase inter-hemispheric coherence of brain oscillatory activity, mainly in fronto-temporal regions, leading to enhancement of functional connectivity across neural networks. The question is whether tPCS can modulate behavior significantly. Our aim was to identify the effects of tPCS on paired associative learning task (PALT) and attention switching task (AST), and to further categorize physiological autonomic responses by heart rate variability and electrodermal activity measurements before and after task performance. Thirty healthy volunteers were randomized to receive a single session of sham or active 2 mA tPCS stimulation with a random frequency between 1 and 5 Hz. We show that active tPCS significantly improved response time in the AST compared to sham stimulation, so that subjects who received active tPCS significantly exhibit decreased switching cost between repeat and switch trials. No differences were found in response accuracy on AST and PALT. No significant changes were observed in physiological parameters. Based on our results, we suggest that tPCS has a more pronounced effect on tasks that require the increase of functional connectivity across pre-existent neural circuitry, rather than on tasks that require the development of new learning circuits or the creation of new connections.